Fluxo duodenal de aminoácidos em bovinos alimentados com dietas contendo ou não extrato tanífero de Acacia mearnsii - Orlandi, Tiago (2013)
This study was conducted to evaluate the effect of including Acacia mearnsii tannin extract in the diet on the flow and amino acid profile in the duodenum of cattle consuming limited amounts of diets containing high degradability protein supplements. Two experiments were conducted in vivo. In trial 1 evaluated the effect of inclusion levels (0, 0.9, 1.8 or 2.7%) of the tannin extract in the diet of four Holstein steers (158 ± 30 kg of body weight (BW )), implanted with cannula in the proximal duodenum and arranged in a randomized 4 × 4 Latin Square. The experimental diets supply was restricted to 2% of BW and consisted of 55% of black oats (Avena strigosa) and 45% of a concentrate containing soybean meal. In trial 2 was evaluated the effect of the inclusion or not of 1.5% of the tannin extract in diet of four Holstein steers (297 ± 56 kg BW), also implanted with cannula in the proximal duodenum and arranged in a randomized 4 × 4 Latin Square. The experimental diets supply was restricted to 2.5% of BW and consisted of 70% of corn silage and 30% of a concentrate containing either soybean meal or canola meal. In both trials the experiment lasted fifteen days, ten days of adaptation diet and five days of sampling. In trial 1 the duodenal flow of the amino acids Ala, Asp, Glu, Ile, Leu, Met, Tyr, Val and all amino acid groups increased (P≤0.05) when tannin extract was added to the diet. However, the profile that arrived in the duodenum was not altered (P>0.05). In trial 2 the duodenal flow of Ala, Arg, Glu, Gly, Leu, Phe, Pro, Thr, Val amino acids and groups of EAA, NEAA, GAA, KAA and TAA increased (P≤0.05) when the tannin extract was added to the diets. An interaction (P≤0.05) was observed between tannin and protein source on the Glu amino acid profile and of GAA group when the mixed soybean meal with tannin increased the percentage these amino acids in the digesta. Moreover, neither the flow nor the amino acid profile of the digesta were affected (P>0.05) by the inclusion of soybean meal or canola meal in the animal diets. A high and significant (P≤0.05) relationship was observed between ingested amino acid profiles and amino acid profiles of duodenal digesta in both trials, and the regression coefficients of the equations of treatments with the inclusion of 1.8 and 1.5% tannin extract (tests 1 and 2, respectively) were statistically equal to 1 (P>0.05). Similarly, the relationships between the EAA profile of duodenal digesta and the EAA profile milk and of muscular tissue were statistically equal (P>0.05) or more next to 1 when added until 1.8% of tannin extract in the diets of trial 1 or when tannin added in the diets in the trial 2. Adding until 1.8% of Acacia mearnsii tannin extract in the diet of animals consuming restricted amounts of foods has the potential to increase the flow of TAA to the duodenum and reduce the difference between the TAA profiles which reaches the duodenum in relation to the ingested TAA profile. Moreover, the inclusion this tannin extract and in this same amount can approximate the EAA profile of duodenal digesta of the EAA profile of the muscular tissue and of milk.